2018
DOI: 10.1016/j.actpsy.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of motor imagery in learning via instructions

Abstract: Learning via instructions and learning through physical practice are complementary pathways to obtain skilled performance. Whereas an initial task representation can be formed on the basis of instructions, physically practicing novel instructions leads to a shift in processing mode from controlled processing toward more automatic processing. This shift in processing mode is supposedly caused by the formation of a pragmatic task representation, which includes task parameters needed to attain skilled task execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…The rationale of this manipulation is that covering a longer physical distance should also increase the time need to imagine making that response (e.g., Decety et al, 1989). In line with Theeuwes et al (2018), we observed a longer time estimation when a larger physical distance needed to be covered. However, although this effect did not differ significantly between covert and overt responding, additional analyses indicated that this distance effect was mainly driven by the overt-practice condition.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The rationale of this manipulation is that covering a longer physical distance should also increase the time need to imagine making that response (e.g., Decety et al, 1989). In line with Theeuwes et al (2018), we observed a longer time estimation when a larger physical distance needed to be covered. However, although this effect did not differ significantly between covert and overt responding, additional analyses indicated that this distance effect was mainly driven by the overt-practice condition.…”
Section: Discussionsupporting
confidence: 71%
“…Logan (1988) assumes that automatic behaviour is attained when task performance is completely determined by episodic retrieval and no longer based on the controlled processing route (see also Logan, 1992Logan, , 2002Schmidt et al, 2016). Theeuwes et al (2018) reported experimental evidence suggesting that covert practice may also lead to the storage of processing episodes. These authors measured the beneficial effect of overtly or covertly practicing new instructions, which related a stimulus (e.g., "rabbit") to a sequence of three responses (e.g., pressing the letter-keys "s," "p," "r").…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these guidelines do not address the processes by which participants create a mental representation of the instructions provided in imagery scripts. However, some insights into this latter issue come indirectly from a recent study by Theeuwes et al (2018). Briefly, these authors developed a paradigm to study how MI affects the selection and retrieval of a novel response sequence.…”
Section: Representing Procedural Instructions In Imagery Scriptsmentioning
confidence: 99%
“…In the new version of the PEP model, we conceptualize such configuration by appealing to simple episodic storage and retrieval processes. Instead of hardwiring instructions, as was done in the previous version of the PEP model, the new PEP version encodes memory traces of the instructed mappings (i.e., decision-to-key mappings and cue-to-task mappings), as a participant will do via, for instance, memory rehearsal or mental imagery ( Ruge & Wolfensteller, 2010 ; see also, Jeannerod, 2001 ; Jeannerod & Frak, 1999 ; O’Shea & Moran, 2017 ; Theeuwes, Liefooghe, De Schryver, & De Houwer, 2018 ). This allows for automatic retrieval during subsequent execution of the task ( Brass, Liefooghe, Braem, & De Houwer, 2017 ; Martiny-Huenger, Martiny, Parks-Stamm, Pfeiffer, & Gollwitzer, 2017 ).…”
Section: Model Descriptionmentioning
confidence: 99%